(3LhGH Yf SDGd aj ebhdg JYGdi (B:" (3jcGO jVF (B"s - (3EHQGgje Hf MSf GdchQGfi GdcQOis; (3GdajQhRGHGOj GdTjQGRj , CHh ESMb EHQGgje Hf Ydj GdTjQGRj, CHh GSMGb , LeGd GdOjf,J (B476 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO abO PcQJ CjOc Gddg Hbhdg JYGdi (B:" (3jcGO jVF Chdh JeSSg fGQ HfGA Ydi Cf gPg GdChUGa eSJMjdI s
(3BNQgG (B:s
(3aEPG CNQL GdaQS Yf Xdg HSQYI de jcf GdXd Ydi hLg GdESJYeGd HebJVi WdH GdeHGOQI ai GdLhGH hGddg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B68s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs